2012
DOI: 10.1089/scd.2011.0161
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cardiomyogenesis in Human Embryonic Stem Cells by Human Embryonic Stem Cell-Derived Definitive Endoderm

Abstract: We previously reported that chick anterolateral endoderm (AL endoderm) induces cardiomyogenesis in mouse embryoid bodies. However, the requirement to micro-dissect AL endoderm from gastrulation-stage embryos precludes its use to identify novel cardiomyogenic factors, or to scale up cardiomyocyte numbers for therapeutic experiments. To circumvent this problem we have addressed whether human definitive endoderm (hDE) cells, which can be efficiently generated in large numbers from human embryonic stem cells (hESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Conversely, supplementation of CHIR during Day 0–1 with high Activin-A (50–100 ng/ml) promoted efficient DE differentiation while strongly inhibiting cardiomyogenesis. Although it is well-established that similarly high levels of Activin-A induce DE, prolonged exposure over several (3–6) days is required [ 23 27 ]. Hence the result in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, supplementation of CHIR during Day 0–1 with high Activin-A (50–100 ng/ml) promoted efficient DE differentiation while strongly inhibiting cardiomyogenesis. Although it is well-established that similarly high levels of Activin-A induce DE, prolonged exposure over several (3–6) days is required [ 23 27 ]. Hence the result in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…20 Protocols mimicking conditions of embryonic cardiac development have been developed to boost the efficiency of cardiomyocyte generation from iPS cells. 21 These include 3-dimensional aggregates of pluripotent stem cells in suspension, known as embryoid bodies (EBs), 20,[22][23][24][25][26][27][28] monolayer differentiation combined with extracellular matrix with growth factors, 29 and inductive co-culture with mouse visceral endoderm-like cell line (END-2) 30,31 . iPS cells are therapeutically attractive given the lack of ethical or immune-rejection concerns.…”
Section: Discussionmentioning
confidence: 99%
“…To date, although many studies have reported that hESCs can be induced to differentiate into ectodermal and mesodermal lineages in vitro, such as neuronal cells and cardiomyocytes [13][14][15][16], reports on endodermal lineage differentiation were relatively less frequent and more inconsistent, especially with regard to pancreatic lineage induction. D'Amour et al reported the induction of hESCs into endocrine cells by mimicking pancreatic organogenesis in vivo following a five-step differentiation process involving definitive endoderm (DE), gut-tube endoderm, pancreatic endoderm, endocrine precursor, and hormone-expressing endocrine cells [17].…”
Section: Introductionmentioning
confidence: 99%